2021
DOI: 10.5492/wjccm.v10.i4.132
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 (COVID-19), viral load and clinical outcomes; lessons learned one year into the pandemic: A systematic review

Abstract: BACKGROUND Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections is diagnosed via real time reverse transcriptase polymerase chain reaction (RT-PCR) and reported as a binary assessment of the test being positive or negative. High SARS-CoV-2 viral load is an independent predictor of disease severity and mortality. Quantitative RT-PCR may be useful in predicting the clinical course and prognosis of patients diagnosed with coronavirus disease 2019 (COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 79 publications
1
61
1
2
Order By: Relevance
“…Different findings about the predictive value of the Ct value have been reported. There are systematic reviews [ 16 , 18 ] indicating a predictive role for morbidity and mortality, but studies have also pointed to a number of weaknesses, such as inter-individual differences in sample-taking, which may result in varying outcomes for specimens [ 19 ]. Moreover, Ct values change over the course of the disease, which renders them dependent on the time of sampling [ 23 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different findings about the predictive value of the Ct value have been reported. There are systematic reviews [ 16 , 18 ] indicating a predictive role for morbidity and mortality, but studies have also pointed to a number of weaknesses, such as inter-individual differences in sample-taking, which may result in varying outcomes for specimens [ 19 ]. Moreover, Ct values change over the course of the disease, which renders them dependent on the time of sampling [ 23 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher is the Ct value, the lower the virus load, and vice versa [ 15 ]. A number of studies found the Ct value to be predictive for mortality and ICU admission [ 16 18 ]. However, respiratory virus load is known to change during the course of infection, indicating the degree of virus shedding in an individual patient.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, there is a correlation between viral load at onset of symptoms and the severity of symptoms of COVID-19. 11 Children have been found to have similar viral loads compared to adults and are known to be efficient spreaders of SARS-CoV-2. 12 …”
Section: Epidemiologymentioning
confidence: 99%
“…Systemic immune-senescence and inflammaging also have damaging effects on the GI tract and dysfunctional gut immune system is associated with severity of lung infections, pneumonia and sepsis through gut lung axis [9,15,28]. The state of gut function and its physiological health, such as dysbiosis, vitamin D deficiency, poor nutrition, obesity, along with COVID-19-related factors, such as viral load, may determine the outcome associated with COVID-19 sepsis [3,12,18].…”
Section: Gut Immune Systemmentioning
confidence: 99%
“…This current COVID-19 pandemic has established that our understanding of the pathophysiology of sepsis remains incomplete and further research is needed to fill these gaps. It has been demonstrated that combinations of risk factors, such as medical comorbidities, older age group, mitochondrial dysfunction, along with high nasopharyngeal viral load, are predictors for worse outcomes [3,4].…”
Section: Introductionmentioning
confidence: 99%